17.0k views
5 votes
•m =x+n/p

•d=f+rx

•-3(x+n)=r

1 Answer

2 votes

Answer:

Explanation:

(1) I'm not sure if the equation is
m = (x + n)/(p) or
m = x + (n)/(p), so I'll solve both below.


m = (x + n)/(p)


mp = x + n


x = mp - n


m = x + (n)/(p)


x = m - (n)/(p)

(2) Answer below


d = f + rx


d - f = rx


x = (d - f)/(r)

(3) Answer below


-3(x + n) = r


x + n = (r)/(-3)


x = (r)/(-3) - n

User Michael George
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.